2015
DOI: 10.1016/j.cell.2015.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of an Epstein-Barr Virus Vaccine Targeting the Receptor-Binding Site

Abstract: SUMMARY Epstein-Barr virus (EBV) represents a major global health problem. Though it is associated with infectious mononucleosis and over 200,000 cancers annually worldwide, a vaccine is not available. The major target of immunity is EBV glycoprotein 350/220 (gp350) that mediates attachment to B cells through complement receptor 2 (CR2/CD21). Here, we created self-assembling nanoparticles that displayed different domains of gp350 in a symmetric array. By focusing presentation of the CR2-binding domain on nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
352
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 320 publications
(361 citation statements)
references
References 56 publications
8
352
0
1
Order By: Relevance
“…The median time to peak titers for EBVgp350 measured by the LIPS assay was much longer (911 days) than the time measured by the ELISA (333 days). In a recent study, we found that mice vaccinated with different gp350 immunogens developed high gp350 ELISA titers relatively early after vaccination but that high gp350 LIPS titers took much longer to develop and required additional doses of immunogen (23). The gp350 LIPS test, an immunoprecipitation assay, is more likely to detect antibody primarily to the native form of the protein, while the ELISA may measure antibodies to both denatured and native forms of the protein (24).…”
Section: Figmentioning
confidence: 99%
“…The median time to peak titers for EBVgp350 measured by the LIPS assay was much longer (911 days) than the time measured by the ELISA (333 days). In a recent study, we found that mice vaccinated with different gp350 immunogens developed high gp350 ELISA titers relatively early after vaccination but that high gp350 LIPS titers took much longer to develop and required additional doses of immunogen (23). The gp350 LIPS test, an immunoprecipitation assay, is more likely to detect antibody primarily to the native form of the protein, while the ELISA may measure antibodies to both denatured and native forms of the protein (24).…”
Section: Figmentioning
confidence: 99%
“…2, a number of vaccine approaches are underdevelopment for the prevention/treatment of most EBVassociated diseases. An effective vaccination program could potentially have significant benefit for the treatment and prevention of a range of EBV-associated diseases, and early clinical studies have provided evidence that vaccination may offer an effective measure to prevent EBV-associated diseases (Cohen 2015;Balfour 2014;Kanekiyo et al 2015). Further studies into the immunological components critical to the establishment of EBV immunity, particularly the role of B cell immunity during primary infection (Panikkar et al 2015a;Hagn et al 2015), and the implementation of more appropriate animal models will also hopefully provide further insight into the immune mechanisms and target antigens that are critical to prevent/control infection (Panikkar et al 2015b).…”
Section: Future Developments In Ebv Vaccine Researchmentioning
confidence: 99%
“…A neutralizing monoclonal antibody against gp42 blocks type 1 gp42 binding more efficiently than type 2 gp42 binding to human cells expressing different HLA class II alleles. Type 1 (top) or type 2 (bottom) gp42 proteins were preincubated with monoclonal anti-gp42 Ab, F-2-1, or a control antibody at room temperature for 30 minutes, and added to human lymphoblastoid cell lines and binding was assayed as described in the legend to Figure 2 except that detection of His-tagged gp42 was performed using rabbit anti-His antibody (Cell Signaling Technology) followed by Alexa488-conjugated (underlined) 5′-GGGCGTGCTAGCCCACCACCACCACCACCACGGAGGAAGAGTGGCCGC-3′ and a reverse primer 5′-CCCGGATCCTCAGGAGTTGCTTCTCTGAGC-3′, digested with XbaI and BamHI and subcloned into the corresponding restriction sites of plasmid CMV/R 8Îşb (VRC 8405) containing a human CD5 signal sequence (41) to yield plasmid CMV/R 8Îşb-gp42. Expi293F cells (Life Technologies) were transfected with plasmid CMV/R 8Îşb-gp42, and gp42-His was purified from the supernatant of the cells using Talon metal affinity resin (Clontech) (42) followed by size-exclusion chromatography using Superose 6 10/300 GL (GE Healthcare Life Sciences).…”
Section: Methodsmentioning
confidence: 99%